COMPARISON OF THE PROVISIONS OF CRIMINAL SANCTIONS AGAINST DRUNKEN PEOPLE WHO COMMIT CRIMINAL ACTS IN INDONESIA AND RUSSIA - Rada Fitriana; Vanny Syafiana Putri (Media Inovasi Pendidikan dan Publikasi, 2023)
The influence of alcoholic beverages on crime is very dominant. The effects of alcoholic beverages are often one of the triggers for someone to commit a crime. The influence of alcoholic beverages is the beginning of the crime. When it is out of control, it can cause a person to commit a crime. This type of research is doctoral in which this research departs from existing rules and then examines it. The approach in this study uses a comparative approach, namely research based on comparing the laws of one country with the laws of other countries. The collection uses secondary legal material, namely looking for legal ideas that exist in certain concepts. based on the principles of the research that the authors conducted, results were found in comparing the laws of the two countries, namely Indonesia and Russia. In the criminal provisions according to Law No. 1 of 2023, there is no prison confinement for drunks who threaten the safety of others and disturb public order, while in Russia sanctions are regulated in the form of imprisonment. So it can be concluded that the existing arrangements in Law no. 1 of 2023, regulates that drunks who threaten the safety of other people or cause trouble are only subject to fines which are light sanctions, unlike the provisions in the Russian Federal Criminal Code which apply criminal witnesses for drunks who commit crimes.